2018
DOI: 10.3389/fmicb.2018.02419
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Nasal Colonization: An Update on Mechanisms, Epidemiology, Risk Factors, and Subsequent Infections

Abstract: Up to 30% of the human population are asymptomatically and permanently colonized with nasal Staphylococcus aureus. To successfully colonize human nares, S. aureus needs to establish solid interactions with human nasal epithelial cells and overcome host defense mechanisms. However, some factors like bacterial interactions in the human nose can influence S. aureus colonization and sometimes prevent colonization. On the other hand, certain host characteristics and environmental factors can predispose to colonizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
329
2
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(396 citation statements)
references
References 167 publications
(242 reference statements)
9
329
2
16
Order By: Relevance
“…Despite the propensity to cause significant morbidity and mortality, S. aureus exists as a part of the microbiota of approximately one-quarter of the population (Sakr et al, 2018); however, colonized individuals are more likely to develop S. aureus-mediated disease (Kluytmans and Wertheim, 2005). In thinking about the dynamics of colonization of the host, S. aureus must interact and compete with the other resident flora as a means to establish itself as a part of the microbiota of a particular niche (Burian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the propensity to cause significant morbidity and mortality, S. aureus exists as a part of the microbiota of approximately one-quarter of the population (Sakr et al, 2018); however, colonized individuals are more likely to develop S. aureus-mediated disease (Kluytmans and Wertheim, 2005). In thinking about the dynamics of colonization of the host, S. aureus must interact and compete with the other resident flora as a means to establish itself as a part of the microbiota of a particular niche (Burian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of commensal bacteria to block pathogen colonization is true at other anatomical locations as well. S. aureus nasal colonization in particular is greatly dependent on molecular interactions with the nasal flora (Brugger et al, 2016;Sakr et al, 2018). Indeed, the nasal cavity is a high salinity and nutrient scarce niche where resident and incoming bacteria compete for limited resources and space in a type of "bacterial warfare" (Krismer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] Several risk factors have been described for S aureus colonization including gender, age, recent hospitalization, ethnicity, genetic predisposition, diabetes mellitus, HIV, haemodialysis, other concurrent skin infections and antibiotic treatment misuse. [34] This study did not identify any 8 statistically significant risk factors that predicted for the pre-operative colonization with S aureus, which was likely due to the small sample size.…”
Section: Discussionmentioning
confidence: 72%
“…In most cases, the nose is the natural reservoir for these organisms. It has also been suggested that there may be an intracellular reservoir . Thus, approximately 40 % of affected patients experience recurrences despite adequate treatment of the primary infection .…”
Section: Resultsmentioning
confidence: 99%